Skala oraz determinanty stosowania systemowego zarządzania w Polsce na tle wybranych krajów Unii Europejskiej, USA, Australii oraz Nowej Zelandii: The scale and the determinants of use of the system management in Poland and in the selected countries of the European Union, USA, Australia and New Zealand - Senkus, Piotr (Management and Administration Journal, 2021)
The system management, that includes some of: quality and environmental management systems is in the recent years, very popular and these systems are the most deployed in the world. Therefore, the article focuses on the presentation of the scale deployment of these systems. Results and themes of implementing the quality and environment management systems in enterprises in Poland, the USA, Australia and New Zealand were also presented. When the certified quality management system according to ISO 9001 is concerned one could see the downward trend, which may be caused by the fact that organizations often seek alternatives that are more appropriate to profile of their activities. The literature identified more than 50 industry-specific quality management systems and alternatives. In addition, one can specify another reason why falling popularity implementation of management systems according to the requirements of ISO 9001, which requires continuous improvement tools, but does not provide for continuous monitoring, According to the data contained in the report ISO Survey 2012, interest in certification of environmental management systems is the prospect for future development in the coming years due to the growing popularity and promotion of environmental protection among international organizations and local governments.